Bank Credit and Agricultural Growth in Zimbabwe: Analysing Effectiveness and Impact - Chikwira, Collin (Acta Universitatis Danubius. Œconomica, 2024)
Objective: The study examines the efficiency and influence of bank loans on Zimbabwe's agricultural growth. The main objectives are to assess how bank lending affects agricultural output and identify the key factors affecting its effectiveness. Approach: This research uses the Vector Error Correction Model (VECM) approach to examine the long-term and short-term relationships between bank credit and agricultural output. Results: Extending credit availability may help agricultural development, as the study indicates a strong long-term positive association between bank credit and agricultural production. However, the short-term study yields inconsistent findings, with variations brought on by outside forces, including shifting policies, unstable economies, and unfavourable weather patterns. This suggests that structural problems in the banking or agriculture sectors impede quick recovery. While bank credit is critical in enhancing agricultural growth in Zimbabwe, its effectiveness is contingent upon a stable economic environment and supportive policies. Implication: Therefore, to maximise the impact of bank lending, policymakers should focus on improving financial infrastructure, mitigating external risks, and creating a conducive environment for agricultural investments. Value: This study uniquely examines the impact of bank credit on agricultural productivity in Zimbabwe using a comprehensive set of economic and non-economic variables and advanced econometric methods, providing new, context-specific insights and practical policy recommendations for enhancing agricultural growth in a challenging environment.